Character Education And The Strategy Of Building An Independent Learners - Hadi, Samsul; Chaer, Moh. Toriqul (EDUCATIO : Journal of Education, 2017)
Education as an institution allows preparing human resources that have the readiness and competence in global competition. Learning program prepares learners with integrative interconnect. In addition, the program language proficiency skills and skills that are hard skills and soft skills. Therefore, strategies are needed education system and school management processes that lead to the formation of character learners. Rationally, character-based education is critical for immediate implementation, therefore, the central issue is examined in writing regarding strategy, a readiness of human resources, indicators of success, design implementation, evaluation strategies, barriers and policy components required. This study used a qualitative approach to presenting the study; (1) The description of the reality of education in Indonesia in general; (2) Strategy to build a new discourse of understanding the implementation of character education based on local wisdom